Evaluation of rapid prenatal human immunodeficiency virus testing in rural cameroon - Granade, Timothy C; Parekh, Bharat S; Tih, Pius M; Welty, Thomas; Welty, Edith; Bulterys, Marc; Ndikintum, George; Nkuoh, Godlove; Tancho, Samuel (Clinical and diagnostic laboratory immunology, 2005)
Pregnant women (n = 859) in rural Cameroonian prenatal clinics were screened by two rapid human immunodeficiency virus (HIV) antibody tests (rapid tests [RT]) (Determine and Hema-Strip) using either whole blood or plasma. One additional RT (Capillus, HIV-CHEK, or Sero-Card) was used to resolve discordant results. RT results were compared with HIV-1 enzyme immunoassay (EIA) and Western blot (WB) results of matched dried blood spots (DBS) to assess the accuracy of HIV RTs. DBS EIA/WB identified 83 HIV antibody-reactive, 763 HIV antibody-nonreactive, and 13 indeterminate specimens. RT results were evaluated in serial (two consecutive tests) or parallel (two simultaneous tests) testing algorithms. A serial algorithm using Determine and Hema-Strip yielded sensitivity and specificity results of 97.6% and 99.7%, respectively, whereas a parallel RT algorithm using Determine plus a second RT produced a sensitivity and specificity of 100% and 99.7%, respectively. HIV RTs provide excellent alternatives for identifying HIV infection, and their field performance could be monitored using DBS testing strategies.